Predictors of repeated high-intensity-effort ability in rugby league players - Gabbett, T. J.; Wheeler, A. J. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To investigate the relationship between repeated high-intensity-effort (RHIE) ability and selected physical qualities in rugby league players. Methods: Sixteen rugby league players underwent measurements of upper-body strength (4-repetition-maximum [4RM] bench press, weighted chin-up, weighted dips), upper-body muscle endurance (body-mass maximum-repetition chin-up, body-mass maximum-repetition dips), lower-body strength (4RM squat), estimated maximal aerobic power (multistage fitness test), and RHIE ability. The RHIE-ability test consisted of 1 × 10-m sprint, 3 × full-contact 1-on-1 tackling efforts, and a 30-m jog recovery. Players performed 4 repetitions of the test, with each repetition completed in 40 second. During the RHIE test, player speed was evaluated with a 10-m sprint effort while the movement of players was recorded using a wearable microtechnology device. 2D Player Load was used to quantify the collision component of the test. Results: Speed decrement was lower for the first- (-2.4% ± 1.0%) than the second-grade (-4.7% ± 2.1%) players. Players with greater initial speed had a higher average speed over the 4 sprints (r = .75), while players with greater maximum-repetition dips maintained a higher 2D Player Load (r = .76). Conclusions: These findings demonstrate a relationship between well-developed acceleration and upper-body muscle-endurance qualities and RHIE ability in rugby league players. Training programs designed to develop acceleration and upper-body muscle endurance are likely to improve RHIE ability.